Conversion of procyclic-form Trypanosoma brucei to the bloodstream form by transient expression of RBP10 - Mugo, Elisha Muchunga; Falk, Franziska; Clayton, Christine (Molecular and biochemical parasitology, 2017)
Bloodstream-form Trypanosoma brucei can lose the ability to differentiate to the procyclic form during prolonged in vitro culture. This can pose a problem during complicated genetic manipulation experiments, especially when the differentiation phenotype is under investigation. Ideally, to preserve differentiation competence, parasites should be cycled after every genetic manipulation step. Conversion of bloodstream-form Trypanosoma brucei to the procyclic form in vitro is routine, but conversion of procyclic forms to bloodstream forms has hitherto only been achieved in transgenic parasites with tetracycline-inducible expression of proteins with RNA-binding domains − either RBP6 or RBP10. This method, however, requires use of a selectable marker which might be needed for other purposes, and restricts options for tetracycline-inducible expression or repression of other genes. A simple method for inter-conversion that does not require permanent genetic manipulation would therefore be useful. Induced expression of RBP10 in procyclic forms gives faster differentiation than expression of RBP6, with a switch towards bloodstream forms within 48h. We here show that bloodstream forms can be obtained by transient transfection of procyclic forms with a circular plasmid designed for expression of RBP10 from an rRNA promoter. This method enables routine cycling of T. brucei without permanent genetic manipulation.